The Hearing Health Care Journey: Putting Beans in Your Cups - Harvey, Michael A. (Seminars in Hearing, 2020)
One of the areas MarkeTrak has explored is the customer journey through hearing health care. The survey has asked question regarding how long they had a hearing loss before they took some type of action, where did they start their journey, why did they obtain hearing instruments or not, and what the hearing instruments cost. To put that journey in perspective, this article looks at the journey of one specific individual and explores their attitudes about their hearing loss through the eyes of a psychologist.
Keywords: hearing loss; psychology of hearing loss; customer journey